Increasing the durability of cold volume stamping equipment - Savytskyi, Y.V.; Mylko, V.V.; Bys, S.S. (Problems of Tribology, 2022)
The work examines the process of cold three-dimensional stamping, which is a very effective method of manufacturing blanks for machine parts. When using cold extrusion, high-cost stamping equipment wears out quickly and defects appear on the finished products. The development of rational technological processes of stamping helps to solve the tasks of expanding the possibilities of cold extrusion by reducing the specific force perceived by the punches, finding the optimal shape of the punch, and testing different grades of steel in order to select them according to the best operational properties. The process of radial extrusion was theoretically investigated and its mathematical model was built based on the energy method, which allows for the analysis of the force mode of extrusion and the kinematics of metal flow, to determine the relative specific force of deformation, to construct the velocity fields for different metal flow zones, and already from these data to calculate the total force deformations The resolution of the model made it possible to formulate recommendations for reducing production defects and increasing the durability of die equipment.